2015
DOI: 10.5326/jaaha-ms-6107
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyosarcoma in the Nasal Vestibule of a Dog: Surgical Excision via a Modified Lateral Approach

Abstract: This case report describes an 11 yr old spayed female German shepherd dog weighing 42 kg that presented with intermittent epistaxis from the left nostril. A nonulcerated pale irregular polypoid mass was visualized within the left nares. Computed tomography revealed a pedunculated mass arising from the ventrolateral nasal mucosal of the left nasal cavity with no evidence of involvement or invasion of adjacent soft tissues or bony structures. Histological and immunohistochemical examination of rhinoscopic biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Diagnosis must always be made histopathologically. McGhie et al [15] reported a case of a nasal angioleiomyosarcoma in a dog recently, which is a differential diagnosis to ALM. In both, histology shows abundant thick-walled blood vessels and smooth muscle cells that are associated with the vessel walls [8].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis must always be made histopathologically. McGhie et al [15] reported a case of a nasal angioleiomyosarcoma in a dog recently, which is a differential diagnosis to ALM. In both, histology shows abundant thick-walled blood vessels and smooth muscle cells that are associated with the vessel walls [8].…”
Section: Discussionmentioning
confidence: 99%
“…The division between angioleiomyoma and leiomyoma is based on the degree of vascularity, with the latter lesion being less vascular (Meher & Varshney 2007). Carpenter & Hamilton (1995) reported a case of angioleiomyoma in the nasopharynx of a dog, and there are only two cases in the veterinary literature of angioleiomyosarcoma observed in the head area (Kheirandish et al 2010, McGhie et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyomas are benign mesenchymal tumours of myogenic origin (Tsobanidou 2006). They are rarely found in the nose because of the paucity of smooth muscle fibres in this location apart from in the wall of blood vessels (Horie et al 2001, Vincenzi et al 2002, Tsobanidou 2006, Gurung et al 2009, McGhie et al 2015. Their exact origin is not yet known (Gurung et al 2009) and three hypotheses have been proposed: leiomyoma arises from the smooth muscle wall of blood vessels or from multipotential mesenchymal cells (Vincenzi et al 2002) or from both (Horie et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation